N-VIVO TEST OF Chlorella vulgaris EXTRACT AS HEAT SHOCK PROTEINS INDUCTION OF CANTANG GROUPER (Ephinephelus fuscoguttatus-lanceolatus) INFECTED BY VIRAL NERVOUS NECROSIS - Amira Masitha; Uun Yanuhar; Asus Maizar Suryanto Hertika (JFMR (Journal of Fisheries and Marine Research), 2019)
Cantang Grouper fish (Ephinephelus fuscoguttatus-lanceolatus) has a high value both in international and local markets. However, these fishes have decreased production due to viral infection of VNN (Viral Nervous Necrosis). In relation to viral infections, heat shock protein (HSP) inducer derived from C. vulgaris is an effort to be used as an anti-inflammatory agent due to VNN infection. The aim of this research to know the potential of C. vulgaris extracts as an inducer of heat shock protein. The method used in this research is experimental method using in-vivo test treatment of C.vulgaris extracts with of 33 μg/ml in Cantang grouper fish with four treatments that are (A) control fish, (B) fish infected with VNN, (C) fish treated with C. vulgaris extracts, and (D) Fish treated with C. vulgaris extracts and VNN infection. The results showed that in the phytochemical test, C. vulgaris extracts showed that there are three compounds contained are alkaloids, terpenoids, and tannins. Control fish was labelled using IgG anti Hsp 70 anti-mouse inflammatory response no apparent inflammatory reaction, fish treated with 33 μg/ml of C. vulgaris extracts HSP-70 responses was low inflammatory response, and fish treated with 33 μg/ml of C. vulgaris extract and VNN inflammatory response strengthened and tissue inflammatory response only with VNN infection were very strong. The results showed the treatment of 33 μg/ml of C. vulgaris extracts can inhibit the development of the virus also capable reduced the inflammatory response to Cantang grouper infected by VNN.